2020
DOI: 10.3390/ph13090219
|View full text |Cite
|
Sign up to set email alerts
|

Towards Better Delivery of Cannabidiol (CBD)

Abstract: Cannabidiol (CBD) has substantial therapeutic potential, but its development as an effective drug by the pharmaceutical industry is hindered by intrinsic characteristics such as low bioavailability, low water solubility, and variable pharmacokinetic profiles. Importantly, lack of patentability of the drug substance also limits the likelihood of an expensive, full development programme in anything other than orphan indications. Potential avenues to overcome these issues with CBD include self-emulsifying drug de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 63 publications
1
118
0
1
Order By: Relevance
“…The high degree of variability in CBD absorption and the resulting pharmacokinetic parameters following CBD ingestion have been previously described [4,12,[18][19][20]. Potential explanations for variable, and often poor, CBD absorption have pertained to properties of the CBD itself (e.g., poor water solubility) and also variability brought about by the significant first pass metabolism it must endure following oral ingestion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The high degree of variability in CBD absorption and the resulting pharmacokinetic parameters following CBD ingestion have been previously described [4,12,[18][19][20]. Potential explanations for variable, and often poor, CBD absorption have pertained to properties of the CBD itself (e.g., poor water solubility) and also variability brought about by the significant first pass metabolism it must endure following oral ingestion.…”
Section: Discussionmentioning
confidence: 95%
“…Following a screening visit consisting of a review of medical history and assessment of body composition, participants reported to the laboratory on five separate mornings in a crossover design. In light of the considerable variability in CBD absorption and the resulting pharmacokinetic parameters following CBD ingestion [4,12,[18][19][20], a crossover design was employed in an attempt to minimize the influence of inter-individual variability. Each morning began with a baseline blood sample and determination of blood pressure, and heart rate variability.…”
Section: Protocol Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These results could also be useful in defining the target dose and ideal length of CBD treatment for these conditions, given the heterogeneous dosages ranging between 200 and 1000 mg and the different treatment durations tested so far. In addition, considering the high variability in the bioavailability of CBD, depending on the route of administration, future research should clarify which are the best treatment approaches for CBD [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical CBD pharmacokinetics studies following oral administration were evaluated in different formulations such as capsules, solutions and oromucosal preparations (42,43).…”
Section: Pharmacokinetic Perspectives Of Cbd Repurposing As Antibacterialmentioning
confidence: 99%